Sosialisasi Penggunaan Social Media untuk Menambah Penghasilan bagi Ibu-Ibu PKK di Desa Lubuk Puar, Bengkulu Tengah - Salsa Billha Sumitha; Tika Saniya; Helmi Herawati (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Lampung, 2023)
Digital media has now become an important medium used in every community. Digital media has become a modern lifestyle, in addition, the use of digital media has helped everyone in doing routines. Individuals, organizations, and even governments are never separated from activities using digital media. The objectives to be achieved from this activity are: to help PKK women in the Lubuk Puar village use social media and the internet wisely, so as to support the creation of a healthy internet in the community; Introducing Prof. Dr. Hazairin, SH University further to residents in the Prof. Dr. Hazairin SH University environment. The benefits of this activity are: PKK mothers at the Lubuk Puar sub-district can be more careful in using the internet and can use it effectively and efficiently and can be used to monitor the use of the internet in their children.